FRI0183 Pregnancy Outcomes in Women Exposed To Infliximab (Innovator). (15th July 2016) - Slater, J.; Phillips, J.; Guo, C.-Y.; Clark, M.; Geldhof, A.; Gearhart, N.; Nissinen, R.
Abstract : Background: Rheumatologic, dermatologic and inflammatory bowel disorders (IBD) can affect women of childbearing potential. Infliximab ([IFX], Innovator) is approved for the treatment of rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), Crohn's disease (CD), ulcerative colitis (UC) and psoriasis (PsO). Objectives: To characterize pregnancy outcomes in patients treated with IFX (Innovator), data obtained from maternal exposure to IFX (Innovator) are presented. Methods: Dataset includes individual patient cases within the company safety database through 23 August 2015. Cases originated from various sources, including spontaneous reporting, clinical studies, and registries. Cases include prospectively reported (ie, pregnancy outcome not known when first reported) maternal exposures to IFX (Innovator) during pregnancy or within 2 months prior to conception with a known pregnancy outcome in RA, PsA, AS, CD, UC, or PsO pts. Birth outcome was stratified by grouped indication. Results: Conclusions: Pregnancy outcomes among pregnancies with T1 IFX (Innovator)-exposure did not differ from the pregnancy outcomes among all prospectively reported pregnancies exposed to IFX (Innovator). Higher percentages of CA were reported among rheumatological indications in comparison to IBD and PsO. The combined rate of CA among pregnancies with IFX (Innovator) exposure was comparable to US general population (3%) 1 . Potential confounders will be further characterized. Limitations of this analysis include lack of a direct comparison group and missing data in the reports. References: Birth Defects. Centers for Disease Control and Prevention. http://www.cdc.gov/ncbddd/birthdefects/data.html . Accessed 14JAN16 Disclosure of Interest: J. Slater Employee of: Janssen Scientific Affairs, LLC, J. Phillips Employee of: Janssen Scientific Affairs, LLC, C.-Y. Guo Employee of: Janssen Scientific Affairs, LLC, M. Clark Employee of: Janssen Scientific Affairs, LLC, A. Geldhof Employee of: Janssen Biologics Europe, N. Gearhart Employee of: Janssen Scientific Affairs, LLC, R. Nissinen Employee of: Janssen Biologics Europe